Improving Shear Strength of Soft Clay by Using Torn Belts Chips - Mekkiyah, Haider Mohammed (Al-Khwarizmi Engineering Journal, 2017)
Random throwing of industrial waste has a significant impact on the environment unless it takes into account the conditions of engineered destroying and/or re-used. Taking the advantage of re-using waste materials in engineering projects represents a well-planned project in order to resolve a lot of engineering problems for some difficult soils. The objective of this study was to evaluate the capability and effects of Rubber Shreds (RS) from scrap torn belts towards improving the shear strength of soft clay. A direct shear tests were conducted on soft clay-RS mixture. The following parameters were investigated to study the influence of RS content, water content, normal stress, and dilation ratio. From experimental test results it was found that previous parameters affecting the shear strength of soft clay. Increasing RS content was found effective in improving the shear strength of soft clay when the normal stress increases provided that fixed water content used in the mixture. Cohesion, c and angle of friction, f were increased by ratio of (1.4-2.3) and (1.5-2) respectively. However, it was revealed that RS content mustn’t exceed the liquid limit level of soft soil. If the water content increases and exceeding the liquid limit level of soft clay, shear strength, cohesion and angle of friction will begin to decrease by reduction percentage of (15%-55%) and (20%-45%) respectively in spite of 30% rubber inclusion. The dilation ratio was highly affected by water content increment; disturbed path of dilation ratio were observed with increasing water content in soil mixture.